(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Financial inclusion has been identified as an essential tool for sustainable development in Sub-Saharan Africa (SSA). The low level of financial inclusion in SSA has been attributed to various factors such as low income, high level of poverty, low literacy rate, and inadequate infrastructure. This research investigates the long-run and short-run relationships between financial inclusion and sustainable development in SSA using a panel vector error correction model (VECM) regression method. The study uses cross-sectional data from 48 countries in SSA, covering the period from 2000 to 2021. The model considers the number of Bank branches per 100,000 adults, automated teller machines (ATMs) (per 100,000 adults), and borrowers from commercial banks (per 100,000 adults) as proxies of financial inclusion, while the sustainable development is proxied by human development index (HDI). In addition, the model controls for the influence of GDP per capita and health expenditure. The regression results show that financial inclusion has a positive and statistically significant association with the level of sustainable development in the SSA region. In the long run, a 1% increase in financial inclusion is associated with a 0.62% increase in sustainable development, while the short-run Wald test indicates that each of lagged values of all independent variables jointly Granger causes changes in HDI, suggesting that financial inclusion variables help predict short-run deviation in HDI. This study’s findings reveal significant statistical evidence of financial inclusion variables in promoting sustainable development. Policymakers can use this information to develop policies that aim to increase GDP per capita, improve access to healthcare services, and financial institutions to promote sustainable development.